Brazil: Maintaining the momentum - Beintema, Nienke M.; Pardey, Philip G.; Avila, Flavio (International Food Policy Research Institute, 2006)
After a period of slow or no growth during the late 1970s and 1980s, public agricultural research investments in Latin America rebounded during the early 1990s.1 These regional trends were heavily influenced by developments in Brazil, which accounted for close to half of the region’s total agricultural research expenditures (Beintema and Pardey 2001). Consequently, developments in Brazilian agricultural R&D are of great significance to the rest of the region and to the developing world more generally.2 But agricultural research investment has grown much more rapidly in Brazil than in many other Latin American countries, reaching intensity ratios close to those found in the developed world.